An Unusual Case of a Double Tricuspid and Mitral Valves Infective Endocarditis Complicated by Multiple Septic Embolisms Secondary to an Atrial Septal Defect: A Case Report and Review of Literature - Caterina Monari; Daniele Molinari; Alessandro Cornelli; Loredana Alessio; Francesco Coppolino; Consiglia Barbareschi; Stefania De Pascalis; Michele Torella; Giovanni Cimmino; Marisa De Feo; Nicola Coppola; Tiziana Formisano (MDPI AG, 2023)
Multivalvular endocarditis (MVE) is an uncommon infection that mostly involves mitral and aortic valves, and it is related to a higher risk of congestive heart failure and a higher mortality. We described a case of a bilateral MVE and performed a review of the literature on similar clinical cases. We reported an unusual case of a 68-year-old male patient with a tricuspid and mitral infective endocarditis due to a methicillin-resistant Staphylococcus aureus complicated by multiple right- and left-sided septic embolization (lungs, brain, spleen, L2-L3 vertebral bones) due to an unknown atrial septal defect identified and repaired during cardiac surgery. Despite the severity of the clinical case, the patient experienced a good clinical outcome also thanks to a multidisciplinary approach. We identified 21 case reports describing bilateral MVE. A multidisciplinary approach is essential in the management of valve diseases to improve the prognosis of patients, especially in bilateral MVE.